Tirotoksična struma jajčnika po ablaciji ščitnice - Takač, Iztok (Acta medico-biotechnica, 2009)
Struma ovarii is a rare type of germ cell tumor and a rare cause of ectopic thyroidal hormonal production. We report a case of laparsocopic management of a thyrotoxic struma ovarii. In a 49-year-old patient, previously treated by ablative surgery and radioactive iodine for Graves' disease, a new onset of hyperthyroidism occurred unexpectedly. A whole-body scan with 131I detected increased pelvic uptake, suggesting struma ovarii. The patient was subsequently treated with laparoscopic bilateral salpingo-oophorectomy. The postoperative course was uneventful. Histopathologic examination revealed the presence of a benign struma ovarii. Three years after treatment the patient is disease free and is receiving thyroid replacement therapy with levothyroxine. In this case the thyrotoxic struma ovarii was diagnosed preoperatively and laparoscopic surgery proved to be a useful and reliable method for ovarian ablation.
Keywords: Hipertiroidizem; Hyperthyroidism; jajčniki; Laparoscopy; Laparoskopija; laparoskopska kirurgija; novotvorbe; Struma jajčnika; Struma Ovarii; tumor